Rosa Plus Emma: Political Pleasure and the Enjoyment of Reason - Murphet, Julian (Filozofski vestnik, 2017)
Today we face broadly the return of an old tension internal to Left politics: a prodigious and rather pleasureless theoretical resurgence of Marxian categories and economic analyses, alongside a febrile activist political culture of occupations, flash mobs and riots. Rather than look to the tired pantheon of usual suspects in conflict (Marx vs Bakunin, Lenin vs Gesell, etc), this essay excavates a pseudo-couple of the far more enabling Deleuzian “and…and…” type, Rosa Luxemburg and Emma Goldman, to see what their juxtaposition might have to offer contemporary debates and disagreements. In focus will be the distinctive part reserved for pleasure—physical, aesthetic, sexual, and sensual—in both their writings, and the structural relationship between it and revolutionary politics as a way of life. The essay seeks to imagine a sustainable left resource of “reason plus enjoyment” that can think against capital whilst persevering with the unconditional demands of a generalized libidinal insurgency. Rosa + Emma = death to Left Puritanism!